ความสัมพันธ์ระหว่างภาระงานกับความเหนื่อยหน่ายในงาน โดยมีกลยุทธ์การเผชิญปัญหาแบบมุ่งเน้นการแก้ไขปัญหาและการสนับสนุนทางสังคมภายในองค์การเป็นตัวแปรกำกับ - สุดาทิพย์ วรเนติโพธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
Job burnout has become more common symtoms which can have a great impact on physical and mental health and work efficiency. In the past, researchers have found that job demands were a cause of job burnout but it can eliminated by accommodate job resources. According to the Job Demands-Resources Model (JD-R model), this study aim to examined and verified the Job Demands-Resources Model which (a) workload as a job demand and (b) social support in the workplace as a job resource. Moreover, this study was added problem-focused coping strategy represents as a personal resource which expected that problem-focused coping strategy would decrease the relation between workload and job burnout. As the purpose of this study was to test the buffering effect of social support in workplace and problem-focused coping strategy on the relationship between workload and job burnout data were collected by an online survey from 260 civil servants in a government sector in Thailand. The results showed a significant three-way interaction (β = -1.55 p < 0.05) where a positive effect of workload on job burnout is diminished when civil servants have high social support and problem-focused coping strategy. The findings provided a theoretical implication by examining an interaction of job and personal resources as a buffering effect on a positive relationship between workload and job burnout.